Effectiveness of awareness program on suicide signals in the community of village health volunteers - Buophun, Sasitorn (Journal of Medical and Public Health Region 4, 2022)
Suicidal behavior It is a problem that is likely to increase in the present day. Therefore, suicide prevention requires cooperation from network partners in the community. This research is a quasi-experimental research. Have a purpose to study the effectiveness of community health volunteers’ awareness-raising and awareness programs on suicidal signals in the villages. The sample consisted of 60 village health volunteers who attended the experimental group and the control group of 30 people each. The experimental group participated in the program 6 times (90 minutes/time, once a week). The control group received regular care. Study in May – July 2019. The tools used include personal information. Awareness questionnaire Recognizing the Signs of Suicide. Using descriptive statistics T-test statistics Repeated measure variance analysis And the Bonferroni pairwise difference test found that both groups had no difference in mean scores on awareness and perception of suicide signs in the pre-trial period. The mean scores of perceptions of suicide signs after the one-month follow-up trial were significantly different at the .01 level. The mean scores of awareness after the experiment were significantly different at the .05 level, while at the 1-month follow-up period, there was no difference. This program can be applied to surveillance of suicide risk groups of people in the community.